Legal Staffing Methods in Resolving Non-Performing Loans in the Banking Industry Based on Prudential Banking Principles - Vidaro, Radhika Althaf; Mulyati, Etty; Harrieti, Nun (International Journal of Science and Society, 2024)
The banking industry is often perceived as the heart and driving force of a country's economy. Given its strategic position, the role of banking as an intermediary institution in collecting and distributing funds to the public for financing economic sector activities is crucial. Based on field practices, debtors often refuse to make payments or settle the credit, which impacts one of the banking health factors, namely the non-performing loan percentage. Legal staffing is essentially a method for resolving credit with a collectibility of 5 and credits that have been written off (Write-Off). The legal staffing method emphasizes resolution principles through non-litigation mechanisms (out-of-court dispute resolution), focusing on the effectiveness and efficiency of case resolution.